The effectiveness of promotional strategy toward the sales improvement of MZ Wealth Saver Plus / Fatin Nadiah Husni - Husni, Fatin Nadiah (Faculty of Business and Management, 2011)
The research of the “Effectiveness 0f Promotional Tools toward the sales Improvement of Mz Wealth Saver Plus” was conducted with four objective which are first to identify the most effective promotional tools made by MCIS Zurich , second to determine relationship between sales promotion and public relation with the improvement of Mz Wealth Saver plus, third to investigate the relationship between advertising and personal selling with sales improvement of Mz Wealth saver plus and lastly, fourth is to identify relationship between direct marketing with the sales improvement. The researcher has used Simple Random Sampling as the sampling technique. In this study, 50 respondents from Melaka have been answered the questionnaire. In this research, descriptive statistic had been used to interpret the data such reliability testing, frequency tables and regression backward table to get the most effective promotional tools. From the finding the respondent agree with the effectiveness of promotional tools which are advertising, sales promotion, public relation and personal selling practiced by MCIS Zurich. While the most effective promotional tools is personal selling which the respondent most agree that this tool can influence the sales improvement of Mz Wealth saver plus. Most of promotional tools used by MCIS Zurich have positive relationship. But not all the tools have significant and strong relationship. There are several tools that not have significant and weak relationship with all level (P value is significant at 0.10 level, P value is significant at 0.05 level, P value is significant at 0.01 level). Other than that the research also gave some recommendation for MCIS Zurich such as implementing more aggressive promotional, focusing and improving on personal selling and provide more benefits and free gift that can attract the customer and also can improve the sales of product.